Reduction of liver fibrosis by rationally designed macromolecular telmisartan prodrugs. (November 2018) - Golder, Matthew; Liu, Jenny; Andersen, Jannik; Shipitsin, Michail; Vohidov, Farrukh; Nguyen, Hung; Ehrlich, Deborah; Huh, Sung; Vangamudi, Bhavatarini; Economides, Kyriakos; Neenan, Allison; Ackley, James; et al.
Abstract At present there are no drugs for the treatment of chronic liver fibrosis that have been approved by the Food and Drug Administration of the United States. Telmisartan, a small-molecule antihypertensive drug, displays antifibrotic activity, but its clinical use is limited because it causes systemic hypotension. Here, we report the scalable and convergent synthesis of macromolecular telmisartan prodrugs optimized for preferential release in diseased liver tissue. We have optimized the release of active telmisartan in fibrotic liver to be depot-like (that is, a constant therapeutic concentration) through the molecular design of telmisartan brush-arm star polymers, and show that these lead to improved efficacy and to the avoidance of dose-limiting hypotension in both metabolically and chemically induced mouse models of hepatic fibrosis, as determined by histopathology, enzyme levels in the liver, intact-tissue protein markers, hepatocyte necrosis protection and gene-expression analyses. In rats and dogs, the prodrugs are retained long term in liver tissue, and have a well-tolerated safety profile. Our findings support the further development of telmisartan prodrugs that enable infrequent dosing in the treatment of liver fibrosis. Macromolecular telmisartan prodrugs optimized for preferential release in fibrotic liver tissue reduce liver fibrosis in mouse models, and are retained and well tolerated in the liver tissue of rats and dogs.